2008
DOI: 10.1088/0964-1726/17/01/015025
|View full text |Cite
|
Sign up to set email alerts
|

Skin design studies for variable camber morphing airfoils

Abstract: This paper identifies the desirable attributes of a flexible skin of a morphing wing. The study is conducted using airfoil camber morphing as an example. The ideal flex-skin would be highly anisotropic, having a low in-plane axial stiffness but a high out-of-plane flexural stiffness. Reduced skin axial stiffness allows morphing at low actuation cost. However, for some substructure and actuation designs, a lower limit on the skin's in-plane axial stiffness may be required to prevent unacceptable global camber d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
82
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(90 citation statements)
references
References 11 publications
5
82
0
1
Order By: Relevance
“…Various journal articles have been published on active flow control using different aerodynamic devices. For example; micro-tabs [38][39][40][41][42][43], Rigid trailing edge flap [44,45], deformable trailing edge flap (DTEF) [14,24,[44][45][46][47][48][49][50][51][52] and morphing trailing edge [44,45,[53][54][55][56][57][58]. Upwind Offshore NREL 5MW wind turbine [59] has been used extensively to investigate reduction of load on multi megawatts turbine [14, 45, 49-52, 60, 61].…”
Section: Aerodynamic Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Various journal articles have been published on active flow control using different aerodynamic devices. For example; micro-tabs [38][39][40][41][42][43], Rigid trailing edge flap [44,45], deformable trailing edge flap (DTEF) [14,24,[44][45][46][47][48][49][50][51][52] and morphing trailing edge [44,45,[53][54][55][56][57][58]. Upwind Offshore NREL 5MW wind turbine [59] has been used extensively to investigate reduction of load on multi megawatts turbine [14, 45, 49-52, 60, 61].…”
Section: Aerodynamic Devicesmentioning
confidence: 99%
“…Implementation of morphing trailing edge flap on wind turbine blades is an idea that originated from the design of morphing aircraft wings and helicopter blades [26,[55][56][57][58]. The blade design is made of two portions as shown in Fig.7; detachable flexible rear part and fixed fore part.…”
Section: Morphing Trailing Flapmentioning
confidence: 99%
“…A highly anisotropic skin is the ideal skin for a morphing aircraft according to Gandhi et al, because it will prevent skin sections between supports from undergoing local bending deformations and sections of the skin in compressive loading from undergoing buckling (Gandhi and Anusonti-Inthra 2008). It was observed that airfoil with a low skin axial stiffness is able to camber easily.…”
Section: Composite Platementioning
confidence: 99%
“…Some studies on the design of airfoils with controllable camber involve stack actuators inside a structure that convert and amplify the motion into a change of curvature of the airfoil [19,20].…”
Section: Applicationsmentioning
confidence: 99%